SPEECH ACTS PREFERENCE IN COMPUTER â MEDIATED INTERCULTURAL COMMUNICATION VIA FACEBOOK MESSENGER: A NETNOGRAPHIC STUDY - Nugraha, Yehezkiel Adhi (English Teaching Journal, 2015)
Â Â Â Â Â Â Â Â Â Â People will not only use language for sharing message but also due to do an action. Through language, people will ask, promise, refuse, greet, invite, thank, and so on. The purpose of this research is to identify the speech acts preference used by Indonesian and Filipino non â native speakers of English via Facebook Messenger. Besides, to identify the similar or different of speech acts preference they used.Â Â Â Â Â Â Â Â Â Â Â The source of data are utterances of conversation in Facebook Messenger. The researcher applies documentation and an observation (reading the book and internet as the references) in collecting the data. After collecting the data, the researcher analyzes the data by focusing the speech acts theory. In order to support the evidence of the result, the researcher needs to describe and compare the high context-cultures and low context-cultures by Hall (1976) and also cultural dimension of Indonesia and Philippines by Hofstede.The result of the analysis shows that the most speech acts preference used by Indonesian and Filipino non - native speakers of English is direct speech act. Similar and different types of speech acts are found. The similar speech act preferences are found in declarations and representatives. The different speech acts preferences are found in expressives, directives, commissives, direct, and indirect speech acts. The result of this research also shows that the communication of Indonesian and Filipino are included into low contex-cultures. It is contrary with the theory of Hall and Hofstede which shows that Indonesia and Philippines factually should be high context-cultures.